All Set for Efficient and Reliable Perovskite/Silicon Tandem Photovoltaic Modules?. Issue 3 (6th September 2021) - De Bastiani, Michele; Babics, Maxime; Aydin, Erkan; Subbiah, Anand S.; Xu, Lujia; De Wolf, Stefaan
Abstract : Over the past few years, perovskite solar cells have arisen as a technology to potentially side with mainstream silicon photovoltaics (PVs) to help drive the transition towards renewable sources of energy. The coupling of perovskites with silicon in a tandem configuration may accelerate this development due to the remarkably high power conversion efficiencies possible with such devices. However, most of the perovskite/silicon tandem achievements so far have been confined to the lab environment, with only a few reported tests under outdoor conditions, using packaged devices. Nevertheless, one of the major challenges for perovskite/silicon tandem technologies, in addition to scale‐up, lies in the cell‐to‐module (CTM) translation, which for the perovskite/silicon tandem concept is complicated by perovskite‐imposed constrains such as a low‐temperature resilience, imposing challenges regarding tabbing and lamination, as well as a high sensitivity to moisture ingress, mandating the search for adequate encapsulation materials and methods. Herein, these challenges are described and assessed in depth and a perspective on future directions toward module design, tailored for perovskite/silicon tandem PVs is given, combining high performance with excellent durability. The discussion also holds relevance for all‐perovskite and other emerging PV technologies seeking market entry. Abstract : Perovskite/silicon tandem solar cells are a cost‐effective technology with a promising future as mainstream photovoltaic technology. Currently, many efforts are placed to further improve the performances of the tandem module. However, little is known about the module requirements for this technology. Here, the main challenges towards tandem module manufacturing are discussed, in view of a swift commercialization of this technology.